KELAYAKAN BUKU CERITA ANAK KARYA MAHASISWA PGSD UNESA UNTUK PEMBELAJARAN APRESIASI SASTRA - Maryam Isnaini Damayanti; Wahyu Sukartiningsih; Hendratno Hendratno; Heru Subrata; Susetyo Rukmi; Nurul Istiq’faroh (Jurnal Education and Development, 2023)
Being able to write a child's story is one of the competencies that must be mastered by prospective elementary school teachers. Through the story written, a teacher can also form the character of his students without being patronizing. Children's stories function to smooth the taste in students, enrich the mind, and equip with other forms of skills. In addition, it also fills the inner wealth of students with the moral values of life. For that, children's story work written by students needs to be analyzed for eligibility. Through this study, analyzed the feasibility of 36 children's stories in a book entitled "Hamchi in the Dwarf's Nest" written by students in the class of 2018C majoring in S1 PGSD FIP Surabaya State University. Data collection is done by documentation techniques using children's story feasibility assessment instruments that are developed into 5 aspects of assessment, namely language, story titles, story content, story characters, and moral messages. The results of the processing and analysis of data were 6 children's stories (17%) worthy categories and 30 other children's stories (83%) very viable categories. It found several themes according to the needs and characteristics of students carried in the child's story. Especially in the development and strengthening of student character. It can be concluded that all children's stories written are worthy of learning Literary Appreciation in elementary school.